Ion channel mutations and cancer - Xinyu Cao; Liang Yan; Liang Hong (Biochemistry and Biophysics Reports)
Cancer is characterized by uncontrolled growth and spread of abnormal cells, driven by genetic, environmental, and lifestyle factors. Genetic mutations contribute to hallmark processes of cancer progression such as sustained proliferation, apoptosis resistance, and immune evasion. Ion channels are pore-forming transmembrane proteins that regulate ion transport across cellular membranes, influencing various cellular functions. Recent studies have indicated the emerging roles of ion channel proteins in cancer. Ion channels are critical for cellular processes like proliferation, apoptosis, migration, and angiogenesis, and dysregulation of ion channels by genetic mutations disrupts these processes, enabling tumor growth, invasion, and metastasis. Ion channel gene mutations have been associated with various cancer subtypes. These ion channel mutations either dysregulate ion channel activity associated with intracellular signaling pathways in cell survival and division, or influence the tumor microenvironment by modifying pH, oxygenation, or ion concentrations, which might facilitate tumor growth and gene expression and contribute to oncogenesis. In the present review, we discuss ion channel regulation of cancer biology and summarize recent studies in ion channel mutations associated with cancer.